Indicators of environmental variability in spring bread wheat cultivars under the conditions of Tyumen Province - V. V. Novokhatin; E. V. Zuev; Т. V. Shelomentseva; Т. A. Leonova (Труды по прикладной ботанике, генетике и селекции)
Background. Among wheat breeding trends, the Research Institute of Agriculture for the Northern Trans-Ural Region prioritizes selection of new source material and development of cultivars with improved agronomic traits and higher resistance to biotic and abiotic environmental stressors. The breeders also pay attention to environmental plasticity of the cultivars.Materials and methods. A field study of 362 spring bread wheat accessions from VIR was performed in the fields of the Research Institute of Agriculture for the Northern Trans-Ural Region in 2011–2016 under contrasting climate conditions. Thirty genotypes were identified for a set of useful agronomic traits. The data were processed using mathematical statistics methods. Rank correlation coefficients, plasticity indices (bi), yield ranges (d, %), homeostaticity (H-st), homeostasis (Hom), and responsiveness coefficients (Kp) were calculated.Results. It was established that cultivars with potentially high yield, plasticity, and strong response to changing environmental conditions: ‘Altaiskaya 110’ (k-65128), ‘Bashkirskaya 28’ (k-64852), ‘AC Pollet’ (k-64975), ‘Chelyaba 75’ (k-64871), ‘Aletch’ (k65011), and ‘Struna Mironovskaya’ (k-65016), may be recommended for breeding intensive cultivars. Accessions with low levels of plasticity and less pronounced environmental variability indices, but tolerant to deteriorated environmental conditions: ‘Tarskaya 10’ (k-64996), ‘FPCh-Рpd-0s’ (k-65123), and ‘Novosibirskaya 44’ (k-64867), can be used to produce climateresistant cultivars.Conclusion. The Ymax, d, V and Kp indicators should be applied for preliminary assessment of cultivars for yield variability, as they are positively correlated to each other and provide quite significant information. Such complementary indicators as bi and S2di, H-st and Hom, positively associated with each other and having a multidirectional effect, are effective for comprehensive assessment of cultivars for environmental variability.